Good Housekeeping Timeless Beauty : Look and Feel Ten Years Younger - Glanville-Blackburn, Jo (London Harper Collins Publishers, 2001)
Covering both instant and long term tips in skincare, bodycare, haircare and make-up, this book provides tried and tested advice about ageless beauty. Each chapter includes a basic guide to a daily regime, with information on targeting specific zones and an anti-ageing workout.
Include Colour Illustrations, Glossary and Index
Keywords: Beauty, Personal -- Health